2019
DOI: 10.3389/fphar.2019.00661
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Mechanisms of Herbal Medicines Against Insulin Resistance: A Review

Abstract: Insulin resistance is a condition in which insulin sensitivity is reduced and the insulin signaling pathway is impaired. Although often expressed as an increase in insulin concentration, the disease is characterized by a decrease in insulin action. This increased workload of the pancreas and the consequent decompensation are not only the main mechanisms for the development of type 2 diabetes (T2D), but also exacerbate the damage of metabolic diseases, including obesity, nonalcoholic fatty liver disease, polycy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 274 publications
(177 reference statements)
1
27
0
1
Order By: Relevance
“…[140] C2C12 cells have been utilised to assess the potential of various natural and drug compounds in relieving metabolic conditions. A number of natural and drug compounds have gained attention due to their favourable effects in insulin resistance, [141] anti-ageing, [142][143][144] muscle atrophy [145,146] and hyperlipidaemia. [147,148] For example, previous review showed that natural products, such as Zengye Decoction, Seyoeum, Wu-Mei-Wan, Erchen Decoction, Linguizhugan Decoction, Fenugreek seed, mulberry leaf and Jinlida, could improve insulin resistance in vitro or in vivo.…”
Section: Role Of Rosmentioning
confidence: 99%
“…[140] C2C12 cells have been utilised to assess the potential of various natural and drug compounds in relieving metabolic conditions. A number of natural and drug compounds have gained attention due to their favourable effects in insulin resistance, [141] anti-ageing, [142][143][144] muscle atrophy [145,146] and hyperlipidaemia. [147,148] For example, previous review showed that natural products, such as Zengye Decoction, Seyoeum, Wu-Mei-Wan, Erchen Decoction, Linguizhugan Decoction, Fenugreek seed, mulberry leaf and Jinlida, could improve insulin resistance in vitro or in vivo.…”
Section: Role Of Rosmentioning
confidence: 99%
“…GLUTs, PI3K, AMPK, and MAPKs involved in the insulin signaling pathway (Li et al, 2019). Given the clinical significance of GQD in treating T2DM, in-depth study on the molecular mechanism of GQD in regulating glucose and lipid homeostasis to improve IR may provide theoretical basis and treatment guidance.…”
Section: A B Cmentioning
confidence: 99%
“…Natural supplements probably represent an ideal source to explore safe and effective agents for the treatment of IR (Kouzi, 2015;Li et al, 2019). The flower of Edgeworthia gardneri Wall.…”
Section: Introductionmentioning
confidence: 99%